INTRODUCE LOCAL WISDOM TROUGH TERNATE’S TRADITIONAL GAMES - Djumati, Rahma; Januarti, Ulfa Dwi (Kantor Bahasa Maluku Utara, 2023)
Ternate, a city in North Maluku possesses abundance of local wisdoms with many variety of types. One type of the local wisdoms is traditional games or permainan rakyat as the people of Ternate called them. Folk games or commonly termed as traditional games are type of local wisdom where still exist in Ternate but rarely practiced by nowadays children along with the emergence of online games which are grasping harder in influencing the type of children games today. This problem raises an issue for maintaining local wisdom values for children through Ternate’s traditional games. The identified data were then be analysed by a literary perspective value theory and by a qualitative descriptive research method. Data collection was conducted by interview and documentation technique. This study found approximately 7 (seven) folk games originated from the people of Ternate, North Maluku. Among them are 1) fortress game (permainan benteng); 2) boi tampurung game; 3) dodorobe game, 4) falinggir game; 5) sem game; 6) mereka pusat game; 7) jilo-jilo game; and 8) cenge-cenge game. These types of folk games are rarely practiced by Ternate children and the disappearance of the cultural practice from these folk games is a sign of the loss of local wisdom values of the community. Therefore, cultural preservation of these folk games need to be addressed to make them remain sustainable and able to maintain their values in the local community.